2021
DOI: 10.1111/scd.12592
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of oral health educational media innovation for visually impaired children: Which one brings the best impact of change?

Abstract: Aim Various innovations of oral health education media were used to bring an impact on oral health behavior and status among visually impaired children. This paper was aimed to systematically investigate which innovation brings the best impact of change. Methods A systematic searching strategy in Scopus, PubMed, ProQuest, ScienceDirect, EBSCO, SAGE, and Cochrane Library database was applied in this study, then followed Preferred Reporting Items for Systematic Reviews and Meta‐Analyses guideline. Studies from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 23 publications
2
8
0
1
Order By: Relevance
“…This territory is unexplored for delivering OHE for visually impaired children. Nevertheless, the included SRs mostly concluded that a combination of different OHE methods mentioned above provided better outcomes of oral hygiene than one method alone 14,15,17,18 and one method was not superior to the other methods when used alone. Among the included reviews, the one 14 that was assessed to be of moderate certainty of assessment found "very low" evidence comparing Braille versus audio-tactile, audio versus Braille, audio-tactile versus audio-tactile-braille and audiobraille versus audio-tactile.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This territory is unexplored for delivering OHE for visually impaired children. Nevertheless, the included SRs mostly concluded that a combination of different OHE methods mentioned above provided better outcomes of oral hygiene than one method alone 14,15,17,18 and one method was not superior to the other methods when used alone. Among the included reviews, the one 14 that was assessed to be of moderate certainty of assessment found "very low" evidence comparing Braille versus audio-tactile, audio versus Braille, audio-tactile versus audio-tactile-braille and audiobraille versus audio-tactile.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, seven articles were included in the present umbrella review. [12][13][14][15][16][17][18] The value of Cohen's kappa was calculated to be 0.847, indicating a substantial level of agreement. 19 The flow diagram for the study selection process is depicted in Figure 1.…”
Section: Selection Of Srsmentioning
confidence: 99%
See 2 more Smart Citations
“…Penelitian lain juga menyebutkan Kombinasi media pendidikan kesehatan gigi dan mulut dapat melibatkan berbagai indera pembelajaran. Karena dampaknya terhadap peningkatan perilaku dan status kesehatan gigi dan mulut pada anak (Maulanti & Nurmala, 2021), tidak hanya itu saja ternyata media pendidikan juga dapat meningkatkan pengetahuan dan pemahaman masyarakat terhadap kasus-kasus yang sering muncul di masyarakat sebagai suatu permasalahan seperti gizi, imunisasi dan pneumonia (Solikhah et al, 2021). Adapun topik yang menarik untuk dibahas saat ini adalah berkaitan dengan media Pendidikan yang diberikan pada anak-anak harus sesuai dengan respon fisiologis anak (Porter et al, 2022) bisa kita lihat dari kecendrungan orang tua yang menggunakan tablet untuk membantu anak tidur.…”
Section: Analisis Kata Kunciunclassified